El delito de insolvencia alimentaria fraudulenta en el código orgánico integral penal. - Sari Camacho, Wendy Karina (2022)
This degree thesis is entitled: "The crime of Fraudulent Food Insolvency in the Comprehensive Organic Criminal Code", and its interest in developing is due to the realization of a study in view that Fraudulent Food Insolvency is a reality of latent affectation that manifests itself in society generating the violation of the rights and principles that protect children and adolescents. The study carried out shows that there is a behavior on the part of those obliged to pay alimony, aimed at hiding, diminishing and / or simulating a reduction or deviation of their economic income or patrimonial assets with the purpose of not paying a fair alimony. For this reason, it is necessary to understand that the right to food includes all the necessary elements that ensure the life of the child or adolescent, I make it clear that the right to receive alimony not only guarantees access to nutritious, sufficient and healthy food; This alimony must be appropriate for the exercise of fundamental rights, therefore this research shows that the right of children and adolescents to receive fair alimony is being affected. In the present thesis, materials and methods were applied that allowed the development of the investigation, likewise interviews and surveys were carried out with legal professionals, results that served to propose the project of legal reform to the Comprehensive Organic Criminal Code in order to classify as The crime of Fraudulent Food Insolvency is separated and thus guarantee the rights of girls, boys and adolescents who are being affected.